Plant-derived alginate polysaccharide hydrogels in sport and exercise nutrition: implications for carbohydrate metabolism, gastrointestinal integrity, exercise recovery, and athletic performance - Li, P.; Song, Q.; Xu, N. (Frontiers in Nutrition, 2026)
Background: Alginate is a plant-derived polysaccharide used in sport nutrition for its gel-forming properties. Alginate- and pectin-based carbohydrate hydrogels aim to optimize carbohydrate delivery during endurance exercise by modulating gastric emptying and intestinal absorption. However, evidence on their effects on metabolism, gastrointestinal (GI) tolerance, recovery, and performance remains inconsistent.